Keanekaragaman, Dominasi, Persebaran Spesies Penggerek Batang Padi dan Serangannya pada Berbagai Tipologi Lahan di Provinsi Jambi - . Wilyus; Fuad Nurdiansyah; Asni Johari; Siti Herlinda; Chandra Irsan; Yulia Pujiastuti (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2013)
Diversity, domination, and distribution of rice stem borer species and its damage in various land typologies in Jambi Province. The research was conducted to analyze the diversity, domination, species distribution of rice stem borers (RSB) and its damage on various land typologies in Jambi Province. The research was carried out using survey method, from December 2010 until June 2011. Samples of RSB were collected from tidal swamp in Tanjung Jabung Timur District, swampy area in Muaro Jambi District, rainfed lowland in Sarolangun District, irrigated lowland in Merangin District, and irrigated upland in Kerinci District and Sungai Penuh District. The results showed that there were five spesies of RSB found in Jambi Province. Scirpophaga incertulas Walker (yellow stem borer) was the most dominant of RSB, followed by Sesamia inferens Walker (pink stem borer), Chilo suppressalis Walker (striped stem borer), Chilo polychrysus Meyrick (dark-headed stem borer), and Scirpophaga innotata Walker (white stem borer). The distribution of S. incertulas, S. inferens, C. suppressalis and C. polychrysus were in all of rice field in Jambi Province, but that of S. innotata was limited over tidal swamp and rainfield lowland area. The RSB damage rate was lower than economic thereshold.